Developing Cytokine Storm-Sensitive Therapeutic Strategy in COVID-19 Using 8P9R Chimeric Peptide and Soluble ACE2 - Nazerian, Yasaman; Vakili, Kimia; Ebrahimi, Ali; Niknejad, Hassan (Frontiers in Cell and Developmental Biology, 2021)
Currently, the COVID-19 pandemic is an international challenge, largely due to lack of effective therapies. Pharmacotherapy has not yet been able to find a definitive treatment for COVID-19. Since SARS-CoV-2 affects several organs, treatment strategies that target the virus in a wider range are expected to be ultimately more successful. To this end, a two-step treatment strategy has been presented. In the first phase of the disease, when the patient is newly infected with the virus and the cytokine storm has not yet been developed, a chimeric peptide is used to inhibit virus entry into the host cell cytosol (by inhibiting endosomal pH acidification) and viral replication. After the virus entry and decrease of Angiotensin Converting Enzyme 2 (ACE2) level, some people are unable to properly compensate for the ACE2 pathway and progress towards the cytokine storm. In the beginning of the cytokine storm, sACE2 protein is very effective in regulating the immune system towards the anti-inflammatory pathway, including M2 macrophages. Hence, the genes of 8P9R chimeric peptide and sACE2 would be inserted in an episomal vector with a separate promoter for each gene: the chimeric peptide gene promoter is a CMV promoter, while the sACE2 gene promoter is a NF-κB-sensitive promoter. The NF-κB-sensitive promoter induces the expression of sACE2 gene soon after elevation of NF-κB which is the main transcription factor of inflammatory genes. Thus, as the expression of inflammatory cytokines increases, the expression of sACE2 increases simultaneously. In this condition, sACE2 can prevent the cytokine storm by inhibiting the pro-inflammatory pathways. To deliver the designed vector to the target cells, mesenchymal stem cell-derived (MSC-derived) exosome-liposome hybrids are used. Herein, the strategy can be considered as a personalized clinical therapy for COVID-19, that can prevent morbidity and mortality in the future.